A STUDY ON CODE SWITCHING USED BY MALINAU STUDENTS IN LAMONGAN - Ningsih, Senja Sri Wanti; Luthfiyati, Dian (Universitas Islam Lamongan, 2020)
Language is foremost a means of communication used by people to convey their ideas and feelings to others when they talk directly or indirectly. Current phenomenon is common in society the code switching used by individuals who live in a bilingual or multilingual community in which the code switching can occur. The researcher chooses one of Malinau students in Lamongan. Her name is